TEACHER PERSPECTIVES ON AI-DRIVEN GAMIFICATION: IMPACT ON STUDENT MOTIVATION, ENGAGEMENT, AND LEARNING OUTCOMES - Abdullah Alenezi (Інформаційні технології і засоби навчання)
This study delves into the insights and experiences of teachers regarding the influence of AI-driven gamification on student motivation, engagement, and learning outcomes. Through qualitative research methods, teacher perspectives are explored to unravel the multifaceted aspects of AI-enhanced gamification within educational settings. The study identifies several significant themes, including positive perceptions of AI-driven gamification, challenges in implementation, elevated motivation and engagement, enhanced learning experiences, improved learning outcomes, and the complexities of assessing long-term effects.